Concept of Pediatric Feeding Problems From the Parent Perspective. Issue 4 (July 2016) - Estrem, Hayley Henrikson; Pados, Britt Frisk; Thoyre, Suzanne; Knafl, Kathleen; McComish, Cara; Park, Jinhee
Abstract: Purpose: Feeding difficulties in early childhood are common, affecting approximately 25% of typically developing children and up to 80% of children with developmental disabilities. There is no interdisciplinary consensus on the definition of a feeding problem and there is no input from families in the conceptualization. Lack of common language is a barrier to effective communication between clinicians, researchers, and caregivers, and inhibits collaboration. The purpose of this study was to examine the conceptualization of pediatric feeding problems by family caregivers (parents). Study Design and Methods: This study reports an empirical phase of a concept analysis. Data from interviews with 12 parents of children with feeding problems were coded for related concepts, attributes, antecedents, and consequences of feeding problems, and then analyzed for themes within conceptual categories. Results: Conceptual elements across interviews are presented with an emphasis on shared perspectives. Parents related pediatric feeding problems to be a process or journey on which they found themselves for an unknown duration. Common themes of attributes were problematic feeding behaviors of the child, restrictive or selective intake, and child weight or growth concerns. Clinical Implications: Parents conceptualize feeding problems as a condition with symptoms experienced by the child and family that need to be incorporated into family life. In contrast, prior literature coming from providers' point of view presents this problem to be of the child. Nurses can improve care of families with children who have feeding problems by coordinating interdisciplinary, family-centered care. Abstract : Feeding difficulties in early childhood are common, affecting approximately 25% of typically developing children and up to 80% of children with developmental disabilities. Perspectives of parents as caregivers have not been included in how feeding problems are viewed by clinicians. These researchers studied how parents as caregivers of their infants conceptualize pediatric feeding problems.